ANALISIS RETURN SAHAM PERUSAHAAN PERBANKAN DI BURSA EFEK INDONESIA - Frizki Nurmawan; Dhani Ichsanuddin Nur (Jurnal GeoEkonomi, 2022)
The capital market has a role as a means of investing for the public to gain a return. The return expected by investors from investing can be in the form of capital gains/losses or dividends. In the 2015 - 2019 period, although in 2019 the return  increased year on year (YoY), it experienced a decline in 2017 – 2018. This uncertainty in the value of stock returns is not in line with the expectations of investors who want their stock returns to continue to move up. The purpose of this study was to determine whether Earning Per Share (EPS), Operating Costs of Operating Income (BOPO), Loan to Deposit Ratio (LDR) and Non Performing Loans (NPL) can contribute to the Stock Return of Banking Sector Companies listed on the Stock Exchange. Indonesia. The sample in this study is banking companies that have been listed on the Indonesia Stock Exchange for the 2015-2019 period using quantitative data types. The data analysis technique in this study used Multiple Regression Analysis, Normality Test, Classical Assumption Test and Hypothesis Testing. The results indicate that: (1) EPS can contribute to Stock Return, (2) BOPO can contribute to Stock Return, (3) LDR can contribute to Stock Return, while (4) NPL cannot contribute to Stock Return.